5x-0.5=0.5-5x

Simple and best practice solution for 5x-0.5=0.5-5x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x-0.5=0.5-5x equation:


Simplifying
5x + -0.5 = 0.5 + -5x

Reorder the terms:
-0.5 + 5x = 0.5 + -5x

Solving
-0.5 + 5x = 0.5 + -5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '5x' to each side of the equation.
-0.5 + 5x + 5x = 0.5 + -5x + 5x

Combine like terms: 5x + 5x = 10x
-0.5 + 10x = 0.5 + -5x + 5x

Combine like terms: -5x + 5x = 0
-0.5 + 10x = 0.5 + 0
-0.5 + 10x = 0.5

Add '0.5' to each side of the equation.
-0.5 + 0.5 + 10x = 0.5 + 0.5

Combine like terms: -0.5 + 0.5 = 0.0
0.0 + 10x = 0.5 + 0.5
10x = 0.5 + 0.5

Combine like terms: 0.5 + 0.5 = 1
10x = 1

Divide each side by '10'.
x = 0.1

Simplifying
x = 0.1

See similar equations:

| 4.7+2.7= | | 4u+2.7= | | 2q^2-8q+50=0 | | x+9=x+2 | | x=100-2p | | 4/9×5/20 | | 5(2-C)=2(2x-13) | | 2x+125=0 | | 5x+7y=-41 | | 70=5x+13+3x+33 | | (x-15)(x+8)= | | 10-7t-19=7t+31-4t | | 4x-5=5+x | | 3+n=39-2n | | 5/12X5 | | 18(y-1)+12y=-8 | | 3(m-2)=6(m+4)-6 | | 5(2y+1)+7(4y+2)=0 | | 5sinx+12cosx-13=y | | m^3+8m-1=0 | | -50x^2+13=42x-39 | | 5+7y=2x+6+6y | | 4(8-5y)+2y=-40 | | 1(5x)-3=1 | | 7×3/4= | | 7×3/4 | | y-(4y-2)=14 | | 9y+2=7y+8 | | 4x^2-1400=0 | | 2x-7=5-x | | y=5ln*x/x-3 | | 27x=8 |

Equations solver categories